'COMET SIGN' AS FIRST EVIDENCE PREGNANCY ULTRASOUND EUTOPIC - Huamán, Moisés (2015)
OBJECTIVE. To determine the presence of vascular flow in the implantation area (‘comet sign’) by ultrasound before the observation of the gestational sac. MATERIALS AND METHODS. Observational study done in 8 patientswith altered reproductive history and amenorrhea by power Doppler endovaginal ultrasound and human chorionic gonadotrophin β subunit. RESULTS. We identified in the 8 patients the implantation site vessels before the gestational sac was visualized. At such time hCG-b levels were 375 to 730 UI, median 515 UI. CONCLUSION. The first echographic sign of eutopic pregnancy would be the decidual vessels at the site of implantation as demonstrated by power Doppler.